Uro-oncologic patient management during the COVID-19 pandemic: survey findings from an Italian oncologic hub - Luzzago, Stefano (Future Oncol, 2021)
Aim: Patient and worker satisfaction at an oncologic hub during the COVID-19 pandemic has never been reported. We addressed this topic. Methods: We conducted a survey to test the views of patients (n = 64) and healthcare professionals (n = 52) involved with our operative protocol. Results: A moderate/severe grade of concern due to the COVID-19 emergency was recorded in 63% of patients versus 75% of hospital staff. High/very high versus low satisfaction grade about preventive strategies to reduce the risk of SARS-CoV-2 contagion was identified in the patients compared with the hospital staff group. Conclusion: Surgical treatment at a hub center of uro-oncologic patients coming from spoke centers is well accepted and should, therefore, be recommended. Preventive strategies to reduce the risk of SARS-CoV-2 contagion in hospital staff members should be implemented.